Lectures on the Origin and Growth of Religion : As Illustrated by Some Points in the History of Indian Buddhism - Davids, T.W. Rhys, (Brill | Manohar Publishers & Distributors, 2024)
This book was published under the Hibbert Lecture Series, 1881. The volume talks about Buddhism, its origins, and its development as a mainstream religion. The first lecture talks about philosophy during its emerging stage, and it is discussed in parallel to certain concepts which were prevalent before Buddhism such as monotheism, transmigration, pantheism, animism, polytheism, and other reformation made before the establishment of Buddhism, etc. This series also covers the assessment of certain Buddhist canons like Pali pitakas and discusses the fundamental Buddhist concepts such as karma. Also, the hagiographical literature of Buddha and various forms of Buddhism practiced post-Buddha's death are discussed in this lecture series. Overall, this book is written from the perspective of comparative studies with non-Buddhist traditions prevalent during the Buddha's period and afterward.